الإنتاجية والإبداعية في النقد الأدبي المعاصر بين التضافر والتنافر - بن عامر, مريم (مكتبة كلية الأدب العربي والفنون, 2023)
الملخّص: هذا البحث يسلّط الضّوء على دور المؤلف في النّقد الأدبي المعاصر، ويستكشف التّفاعل بين الإنتاجية والإبداع. كما يناقش كيف تتشكّل غرائز المؤلف الإنتاجية والميول الإبداعية في أعماله، وتؤثرعلى العملية الإبداعية الشّاملة. ويستجلي أيضًا الدّوافع والإيحاءات الّتي تقود المساعي الأدبية للمؤلّف.يركز كذلك على سيرورة إنتاج النّص، كما يفحص انفتاح أدب ما بعد الحداثة وخروجه عن الهياكل السّردية التّقليدية، فضلاً عن دور القارئ في النّقد الأدبي المعاصر إذ يتمّ التّحقيق في العلاقة المعقّدة بين النّص والقارئ، مع الأخذ في الاعتبار كيفية تأثير إنتاج النّص على تفسير القارئ وتمتّعه به. بالإضافة إلى ذلك، فإنّه يستكشف مفهوم تذوّق النّص، باستخدام مقاربة جمالية لفهم كيف يدرك القرّاء ويقدّرون العناصر الإبداعية داخل العمل الأدبي. الكلمات المفتاحيّة: المؤلف، القارئ، الإنتاجية، الإِبداعية، نقد ما بعد الحداثة. Summary : This research sheds light on the role of the author in contemporary literary criticism and explores the interaction between productivity and creativity. It discusses how the author's productive instincts and creative inclinations are formed in their works and how they impact the overall creative process. It also examines the motivations and inspirations that drive the literary endeavors of the author. The research also focuses on the process of text production and examines the openness of postmodern literature and its departure from traditional narrative structures. Additionally, it explores the role of the reader in contemporary literary criticism by investigating the complex relationship between the text and the reader, considering how the production of the text influences the reader's interpretation and enjoyment. Furthermore, it explores the concept of textual appreciation, using an aesthetic approach to understand how readers perceive and appreciate the creative elements within the literary work. Keywords: Author, Reader, Productivity, Creativity, Postmodern Criticism.
Keywords: المؤلف، القارئ، الإنتاجية، الإِبداعية، نقد ما بعد الحداثة